Experiences of caregivers of children receiving palliative care at Mzuzu Central Hospital, Malawi - Chaputula, Bertha Mwandida (2021)
The number of children with life threatening and limiting illnesses requiring children palliative care is increasing each and every year. In response to the rising number of children requiring palliative care, family involvement in care giving has expanded. Caregivers play a major role in caring for children with life-limiting or threatening illnesses on palliative care at home as well as in hospital. However, for them to adequately provide the care, they require adequate support.This study reports on the caregivers’ experiences of caring for children receiving palliative care at Mzuzu Central Hospital Palliative Care Clinic. The study was aimed at exploring the caregivers’ experiences of caring for children receiving palliative care. A descriptive qualitative research method was used. The target group was caregivers of children with life threatening or limiting illnesses receiving palliative care at the clinic. A total of 30 caregivers were recruited for the study using purposive sampling technique. Qualitative data was collected using semi structured interview guide for in-depth interviews and a tape recorder while analysis was done using thematic analysis. Findings revealed that caregivers play a major role in caring for their children receiving palliative care. They provide assistance with activities of daily living and health care management in additional to their usual daily chores. The needs of the children receiving palliative care included transportation, finances, information, health care and daily needs. Family members and community members formed part of the caregivers’ support systems. Caregivers of children receiving palliative care reported facing financial, social, physical, and psychological and health service challenges. Proper assessment and availability of adequate support would positively influence the caregiver’s experiences of caregiving and the child’s quality of life. Hence, there is need to develop practical interventions that will lessen the caregivers’ challenges.